Pemodelan Sistem Pengelolaan Sampah Di Tempat Pemrosesan Akhir (TPA) Kabupaten Tana Tidung Dengan Pendekatan System Dynamic - Tini Parmawati; Endang Hernawan; Sri Listyarini (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
ABSTRACT Waste management problems in Indonesia are caused by several factors including inadequate landfills, insufficient composting, and waste management in landfills in the use of the right system. Methods used with a dynamic system modeling approach using powersim software. Waste generation in Tana Tidung District increases as the population increases, with curves shaping Growt's exponential behavior. The results of the study conducted simulations for 33 years (2017-2050) in early 2017 the total population of 23,783 people, waste generation 21,701,987.50 l/year. A pessimistic scenario of 8% waste reduction could extend the life of landfill zones for 5 years until 2031. A moderate scenario of 33.73% waste reduction could extend the life of the landfill zone for 9 years until 2035. An optimistic scenario of 48.336% waste reduction could extend the life of the landfill zone by 18 years until 2044, with curves forming decay behavior. INTISARI Masalah pengelolaan sampah di Indonesia diakibatkan beberapa faktor diantaranya kurang memadainya tempat pembuangan sampah, pengomposan masih kurang, dan pengelolaan sampah di TPA dalam penggunaan sistem yang tepat. Metode yang digunakan dengan pendekatan pemodelan system dynamic dengan menggunakan perangkat lunak powersim. Timbulan sampah di Kabupaten Tana Tidung meningkat seiring peningkatan jumlah penduduk, dengan kurva membentuk perilaku Eksponensial Growt. Hasil penelitian melakukan simulasi selama 33 tahun (2017-2050) tahun awal 2017 jumlah penduduk 23.783 jiwa, timbulan sampah 21.701.987,50 l/tahun. Skenario pesimis prameter pengurangan sampah 8% dapat memperpanjang umur zona landfill selama 5 tahun hingga tahun 2031. Skenario moderat parameter pengurangan sampah sebesar 33,73% dapat memperpanjang umur zona landfill selama 9 tahun hingga tahun 2035. Skenario optimis parameter pengurangan sampah sebesar 48,336% dapat memperpanjang umur zona landfill selama 18 tahun hingga tahun 2044, dengan kurva membentuk perilaku decay.